2021
DOI: 10.3390/ijms22094466
|View full text |Cite
|
Sign up to set email alerts
|

Melanin Transfer in the Epidermis: The Pursuit of Skin Pigmentation Control Mechanisms

Abstract: The mechanisms by which the pigment melanin is transferred from melanocytes and processed within keratinocytes to achieve skin pigmentation remain ill-characterized. Nevertheless, several models have emerged in the past decades to explain the transfer process. Here, we review the proposed models for melanin transfer in the skin epidermis, the available evidence supporting each one, and the recent observations in favor of the exo/phagocytosis and shed vesicles models. In order to reconcile the transfer models, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 75 publications
2
95
0
Order By: Relevance
“…Melanin transfer from melanocytes to keratinocytes is a crucial process for skin pigmentation and photoprotection against UVr-induced cell damage. Our previous studies suggested that coupled exo/phagocytosis is the predominant mechanism of melanin transfer in human skin and showed an essential role for Rab11b and the exocyst tethering complex in this process (Tarafder et al, 2014;Moreiras et al, 2019) 1( 1) . Here we provide evidence that the process of melanin exocytosis is more complex than previously appreciated and demonstrate the existence of at least two types of melanin exocytosis pathways, including a novel one induced by keratinocytes and regulated by the Rab3a small GTPase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melanin transfer from melanocytes to keratinocytes is a crucial process for skin pigmentation and photoprotection against UVr-induced cell damage. Our previous studies suggested that coupled exo/phagocytosis is the predominant mechanism of melanin transfer in human skin and showed an essential role for Rab11b and the exocyst tethering complex in this process (Tarafder et al, 2014;Moreiras et al, 2019) 1( 1) . Here we provide evidence that the process of melanin exocytosis is more complex than previously appreciated and demonstrate the existence of at least two types of melanin exocytosis pathways, including a novel one induced by keratinocytes and regulated by the Rab3a small GTPase.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the coverslips were mounted with Fluoromount-G with DAPI (Invitrogen, Lenexa, Kansas) to visualize the cells' nuclei and images were acquired in a ZEISS Axio Imager 2 microscope with a PlanApochromat 63x1.4 NA oil-immersion objective. The melanin-containing organelles present within keratinocytes, which we proposed to call melanokerasomes (Moreiras et al, 2021b), were counted using ImageJ software and normalized to the number of cells analyzed in each image.…”
Section: Melanin Transfer Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The compartment of melanin taken up by keratinocytes from melanocytes was recently given the name melanokerasome [7,8,[24][25][26][27]. Our previous study comparing hematoxylin and eosin (H&E) stain slice and OCT images revealed melanin appears as hyper-reflective cells with a relatively strong intensity compared with the surrounding tissues [6].…”
Section: Melanin Detectionmentioning
confidence: 99%
“…Studies suggested melanocytes rapidly transfer the produced melanin to keratinocytes rather than accumulating it [7]. This may explain that typical active dendritic melanocytes were hardly observed, while supranuclear melanin caps in the keratinocytes were easily visible [8,9]. Melanin amount and distribution are therefore commonly used to classify the melasma subtypes and to monitor the treatment response [10].…”
Section: Introductionmentioning
confidence: 99%